Measuring Help-Seeking Intentions: Properties of the General Help Seeking Questionnaire - Wilson, Coralie J.; Deane, Frank P.; Ciarrochi, Joseph; Rickwood, Debra (Canadian Journal of Counselling and Psychotherapy, 2007)
Understanding help seeking intentions and behaviour is fundamental to the identification of factors that can be modified to increase engagement in counselling. Despite considerable research on these variables, integrating prior research has been impeded by a lack of consistent and psychometrically sound help-seeking measures. The General Help-Seeking Questionnaire (GHSQ) was developed to assess intentions to seek help from different sources and for different problems. Using a sample of 218 high school students, the GHSQ was found to have satisfactory reliability and validity, and appears to be a flexible measure of help-seeking intentions that can be applied to a range of contexts.